They Work Together to Roar: Kindergartners' Understanding of an Interactive Causal Task. Issue 3 (2nd July 2016) - Solis, S. Lynneth; Grotzer, Tina A.
ABSTRACT: The aim of this study was to investigate kindergartners' exploration of interactive causality during their play with a pair of toy sound blocks. Interactive causality refers to a type of causal pattern in which two entities interact to produce a causal force, as in particle attraction and symbiotic relationships. Despite being prevalent in nature, elementary through college students experience difficulties interpreting interactive causal patterns and tend to resort to simpler, unidirectional explanations of scientific phenomena. Less is known about younger students' nascent conceptions of interactive causality, which can serve as a foundation for advanced science learning. A microgenetic study was conducted to investigate 12 kindergartners' understanding of the interactive nature of the pair of sound blocks. Children's manipulations and explanations of the blocks were analyzed for evidence of unidirectional or interactive reasoning. Ten children produced interactive actions and explanations throughout the study session. The remaining two students shifted from interactive to unidirectional explanations and actions during the session. Children's causal interpretations varied as they focused on different features of the blocks, suggesting that they were attending to evidence of the blocks as they played. These findings inform how teachers may design instructional opportunities that highlight key features of interactive events.